2007
DOI: 10.1086/509147
|View full text |Cite
|
Sign up to set email alerts
|

An X‐Ray Census of Young Stars in the Massive Southern Star‐forming Complex NGC 6357

Abstract: We present the first high spatial resolution X-ray study of the massive star-forming region NGC 6357, obtained in a 38 ks Chandra/ACIS observation. Inside the brightest constituent of this large H ii region complex is the massive open cluster Pismis 24. It contains two of the brightest and bluest stars known, yet remains poorly studied; only a handful of optically bright stellar members have been identified. We investigate the cluster extent and initial mass function and detect $800 X-ray sources with a limiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
141
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(156 citation statements)
references
References 105 publications
(212 reference statements)
14
141
1
Order By: Relevance
“…Considering that we have found 28 (for 3.2 < A V < 7.8) to 85 (for 3.2 < A V < 15) stars down to ∼6.5 M (assuming an age of 1 Myr), a Scalo IMF yields ∼3600 to ∼11 000 members in the Sofi field. This is consistent with ∼10 000 (in fact ∼5000 if the distance is shortened to 1.7 kpc) found by Wang et al (2007) by scaling their derived X-ray luminosity function (obtained from sources on a larger area than our SofI field) to that of the ONC. Thus, the stellar mass of Pis24 core amounts to ∼2−6 × 10 3 M for a Scalo IMF.…”
Section: Star Formation On the Smaller Scale: Stellar Population Of Psupporting
confidence: 90%
See 2 more Smart Citations
“…Considering that we have found 28 (for 3.2 < A V < 7.8) to 85 (for 3.2 < A V < 15) stars down to ∼6.5 M (assuming an age of 1 Myr), a Scalo IMF yields ∼3600 to ∼11 000 members in the Sofi field. This is consistent with ∼10 000 (in fact ∼5000 if the distance is shortened to 1.7 kpc) found by Wang et al (2007) by scaling their derived X-ray luminosity function (obtained from sources on a larger area than our SofI field) to that of the ONC. Thus, the stellar mass of Pis24 core amounts to ∼2−6 × 10 3 M for a Scalo IMF.…”
Section: Star Formation On the Smaller Scale: Stellar Population Of Psupporting
confidence: 90%
“…Assuming a distance of 1.7 kpc and adopting the evolutionary tracks of Palla & Stahler (1999) for 1 Myr old PMS stars, this corresponds to a mass completeness limit of ∼2 M for A V between 5-10 mag, which is consistent with what was found by Wang et al (2007).…”
Section: X-ray Source Population Of Pismis 24supporting
confidence: 85%
See 1 more Smart Citation
“…6) were previously identified, the well-known Pismis 24 and AH03J1726-34.4 (Dias et al 2002). For Pismis 24, Wang et al (2007) identified 34 O-B3 stars from X-ray studies. The information on the cluster AH03J1726-34.4 is very sparse.…”
Section: The Ob Stars Censusmentioning
confidence: 99%
“…the initial mass function (IMF). Although the correlation between stellar mass and X-ray luminosity shows a considerable scatter (see, e.g., , X-ray studies of a large number of young stellar clusters have shown that the XLF appears to be rather universal and constant in different environments (see Feigelson & Getman 2005;Getman et al 2006;Wang et al 2007).…”
Section: The X-ray Luminosity Functionmentioning
confidence: 99%